Structure–Function Relationship in Glaucoma Using Ganglion Cell–Inner Plexiform Layer Thickness Measurements - Rao, Harsha L.; Qasim, Muhammad; Hussain, Raza S. M.; Januwada, Manideepak; Pillutla, Lalitha N.; Begum, Viquar U.; Chaitanya, Aditya; Senthil, Sirisha; Garudadri, Chandra S. (Investigative ophthalmology & visual science, 2015)
To evaluate the structure-function relationship between ganglion cell-inner plexiform layer (GCIPL) thickness at the macula and 10-2 standard automated perimetry (SAP) in glaucoma and to evaluate the relationship using a recently proposed linear model. In a cross-sectional analysis, structure-function relationship was determined in 50 glaucomatous eyes (40 patients, mean deviation: -15.4 ± 7.5 dB) and 21 control eyes (13 subjects, mean deviation: -3.4 ± 3.0 dB), which had undergone 10-2 SAP and GCIPL imaging on the same day. Functional loss was derived from total deviation numerical values on 10-2 SAP and calculated on both a linear (reciprocal of Lambert) and a decibel scale after accounting for the retinal ganglion cell displacement at the macula. Strength of relationship was reported as coefficient of determination (R2) of the linear regression models fitted to the data separately for different sectors. The relationship was also evaluated using a linear model. The R2 for the associations between GCIPL thickness sectors and the corresponding sector SAP total deviation values ranged from 0.19 (for superonasal GCIPL sector) to 0.60 (for average GCIPL thickness) when functional loss was calculated on the decibel scale and 0.16 (for superonasal sector) to 0.54 (for inferior sector) on the linear scale. All associations were statistically significant (P < 0.05). The linear model fitted the data reasonably well. Significant structure-function associations were found between GCIPL thickness measurements at the macula and the functional loss measured on 10-2 SAP in glaucoma. Best fit was found for the inferior and average GCIPL sector thickness. The linear model was useful to study the structure-function relationship.